CO20 | Coagulation alterations as prognostic indicators in septic patients (Bleeding, Thrombosis and Vascular Biology, 2025)
Background and Aims: Sepsis is a major cause of mortality and morbidity globally and, despite advances in diagnostic and therapeutic strategies, it remains a complex condition. In its pathophysiology, in addition to the innate and adaptive immune response, the vascular endothelium also plays a crucial role: indeed, Sepsis Induced Coagulopathy (SIC) and Disseminated Intravascular Coagulation (DIC) significantly increase the risk of mortality. For this reason, early identification of coagulopathy is fundamental to ensure timely and effective patient management.